Flexural capacity enhancement of rectangular high‐strength concrete columns confined with post‐tensioned steel straps: experimental investigation and analytical modelling. (December 2016) - Ma, Chau‐Khun; Awang, Abdullah Zawawi; Omar, Wahid; Liang, Maybelle; Jaw, Siow‐Wei; Azimi, Mohammadamin
Abstract: The load‐carrying capacity and deformability of concrete columns can be substantially enhanced by confining with post‐tensioned steel straps. As interest in high‐strength concrete (HSC) grows among structural engineers and researchers due to its superior performance, this confining technique is being extended to HSC columns with the hope that it can eliminate the undesired properties of HSC, especially its brittleness. However, experimental studies involving confined HSC columns subjected to eccentric loads are comparatively limited. It can be seen from past research that most studies of external confinement were conducted on small‐scale normal‐strength concrete (NSC) cylinders subjected to concentric loads. Since most columns are subjected to eccentric loads in reality, the scarcity of test data has prevented the potential of this confining technique from being fully exploited. In this paper, this confining technique is called the steel‐strapping tensioning technique (SSTT) for brevity. Nine HSC columns were tested under eccentric loads. The specimens were grouped into three groups with each group having an unconfined HSC column as a control specimen, a two‐layer SSTT‐confined HSC column and a four‐layer confined HSC column. The experimental results show that the flexural capacities of HSC columns can be enhanced with SSTT. The deformability of confined HSC columns is significantly improved with such confinement.